2007
DOI: 10.1029/2007gl029253
|View full text |Cite
|
Sign up to set email alerts
|

On the twilight zone between clouds and aerosols

Abstract: [1] Cloud and aerosols interact and form a complex system leading to high uncertainty in understanding climate change. To simplify this non-linear system it is customary to distinguish between ''cloudy'' and ''cloud-free'' areas and measure them separately. However, we find that clouds are surrounded by a ''twilight zone'' -a belt of forming and evaporating cloud fragments and hydrated aerosols extending tens of kilometers from the clouds into the socalled cloud-free zone. The gradual transition from cloudy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
367
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(390 citation statements)
references
References 18 publications
22
367
0
1
Order By: Relevance
“…This particular combination of changes results in a 16% AOD increase near cloud edge at 532 nm wavelength. Sun-photometer measurements from two recent studies yield comparable AOD increase estimates near cloud edge of $10% [Redemann et al, 2009] and $13% [Koren et al, 2007] at visible wavelengths, bearing in mind that our analysis is at night, while theirs is during the day which may cause AOD underestimates due to 3-D radiative cloud-adjacency effects. A simultaneous increase in R j and decrease in N j and s j is consistent with collision-coalescence with larger aerosols removed by precipitation scavenging, although precipitation scavenging may be minimal given that only $5% of these clouds precipitate [Snodgrass et al, 2009].…”
Section: Resultsmentioning
confidence: 86%
“…This particular combination of changes results in a 16% AOD increase near cloud edge at 532 nm wavelength. Sun-photometer measurements from two recent studies yield comparable AOD increase estimates near cloud edge of $10% [Redemann et al, 2009] and $13% [Koren et al, 2007] at visible wavelengths, bearing in mind that our analysis is at night, while theirs is during the day which may cause AOD underestimates due to 3-D radiative cloud-adjacency effects. A simultaneous increase in R j and decrease in N j and s j is consistent with collision-coalescence with larger aerosols removed by precipitation scavenging, although precipitation scavenging may be minimal given that only $5% of these clouds precipitate [Snodgrass et al, 2009].…”
Section: Resultsmentioning
confidence: 86%
“…For example, Koren et al (2007) showed that a belt of forming and evaporating cloud fragments and hydrated aerosols, extending kilometers away from the clouds into cloud-free areas could, have major implications on the estimation of Earth's radiation budget. This phenomenon has been termed the "twilight zone".…”
Section: Introductionmentioning
confidence: 99%
“…[5] From the ground, Koren et al [2007] showed that AOD retrieved from AERONET sunphotometers [Holben et al, 1998] decreases with time after the passage of clouds, while Angstrom exponent increases. Chiu et al [2009] used the Atmospheric Radiation Measurement (ARM) Shortwave Spectrometer (SWS) measurements to study the transition zone between cloud-free and cloudy areas.…”
Section: Introductionmentioning
confidence: 99%
“…[3] From satellites, many studies found that the brightness of cloud-free areas systematically increases near clouds [Ignatov et al, 2005;Loeb and Manalo-Smith, 2005;Matheson et al, 2005;Zhang et al, 2005;Koren et al, 2007;Loeb and Schuster, 2008]. The enhanced brightness can result from several factors [Twohy et al, 2009;Varnai and Marshak, 2009], including: small-cloud contamination [e.g., Zhang et al, 2005]; cloud-aerosol microphysics like swelling and increase of number concentration of aerosols in the humid environment near clouds [e.g., Su et al, 2008]; and three-dimensional (3D) radiative interactions between clouds and surrounding clear areas [e.g., Wen et al, 2007;Marshak et al, 2008].…”
Section: Introductionmentioning
confidence: 99%